ROLE OF EXCLUSIVE BREASTFEEDING AND S-IGA ANTIBODIES ANTIROTAVIRUS BREAST MILK TOWARDS RISK OF ACUTE ROTAVIRUS DIARRHEA IN INFANTS AGE OF 1-6 MONTHS: DO THEY CORELATE TO BREASTFEEDING "DAILY DOSE" AND ANTIBODY TITERS? - Lely, Oka; -, Soetjiningsih; Wibawa, I D. N.; Mantik Astawa, IN (INDONESIAN JOURNAL OF BIOMEDICAL SCIENCES; Vol. 6, No. 1 Januari 2012, 2012)
ABSTRACT Exclusive breastfeeding reduces the incidence of diarrhea, especially in children who live in densely populated neighborhood. This study aims to determine the relationship between exclusive breastfeeding and breast milk contains antirotavirus s-IgA antibodies towards risk of acute rotavirus diarrhea in infants aged of 1-6 months. Case-control study design is applied to determine the relationship between exclusive breastfeeding and breast milk contains s-IgA antibodies antirotavirus with risk of acute rotavirus diarrhea. Cases in this study were patients with acute rotavirus diarrhea and controls were patients without acute rotavirus diarrhea. Cases and controls were matched based on age. There were 23 cases and 69 controls. The proportion who received exclusive breastfeeding was 34.8% in cases and 34.4% in controls, with OR of 1.21 (95% CI: 0.45 to 3.28) and p = 0.28. Breast milk contains sIgA antibodies antirotavirus for case was 17.39% and controls was 23.2%, OR was 1.12 (95% CI: 0.29 to 4.29), p = 0.203. In conclusion, exclusive breastfeeding and breast milk contains sIgA antibodies antirotavirus were not associated with risk of acute rotavirus diarrhea in infants 1-6 months. This may be caused by differences in population and demographic studies as well as low of milk sIgA antibody antirotavirus titters. Further research of breastfeeding regardless of antirotavirus containing high antibody titters sIgA is needed.
Keywords: exclusive breastfeeding, antirotavirus s-IgA antibodies, the risk of acute rotavirus diarrheal.